Eficiencia del carbón activado procedente del residuo agroindustrial de coco (Cocus nucifera) para remoción de contaminantes en agua - Bravo Moreira, Katherine Ivette (2017)
The objective of the research was to evaluate the efficiency of the activated carbon from the agroindustrial residue of coconut in the removal of contaminants in water. Coconut shell from the Pimpiguasi site, Portoviejo, was used for the production of activated carbon by physical activation at a temperature of 700°C for one hour. As a result, 823.5g was obtained in the production of activated charcoal, of which 525g was used in the experimental units. The experimental scheme was a completely randomized design with three treatments and three replicates of 100, 50 and 25 grams of activated carbon filtering one liter of synthetic water composed of 1g of silty soil and 0.0025g of chlorine, nine filters were made as units Experimental. Physical analyzes were performed on water: suspended solids, residual free chlorine, turbidity, color and pH. The percentages of removal resulting from the evaluated parameters were processed in the statistical software InfoStat version 2016, to perform the analysis of variance and Tukey test. The parameters of residual free chlorine and suspended solids presented significant differences, contrary to pH; However, turbidity and color present both differences and significant similarities between treatments, projecting treatment of 100g of activated carbon as the most efficient (75.68%) in the removal of contaminants from the water. The economic feasibility of the treatment with better efficiency was studied by means of the method of cost of production; establishing a price of $ 23.26 per treatment, which includes filter construction and activated carbon processing.